Factors Influencing Word-of-Mouth Behaviour at Outpatient Department YPK Mandiri Hospital, Jakarta - Liem, Raissa; Fernando, Darrell; Bernarto, Innocentius (Indonesian Journal of Obstetrics and Gynecology, 2023)
The purpose of this study was to determine the factors that influence the word-of-mouth behavior of patients seeking treatment at YPK Mandiri Hospital, Jakarta. The factors studied were doctor's expertise, doctor's communication, nursing, ancillary, and administration services, hospital reputation, and the physical structure and facilities of the hospital. Data were collected by a questionnaire distributed to patients receiving outpatient treatment. The number of samples obtained is 162 samples. A convenience sampling technique was used in this study. Data analysis was performed using the Partial Least Square-Structural Equation Modelling (PLS-SEM) approach using SmartPLS software. The results showed that doctors’ expertise, doctors’ communication, hospital reputation, and the physical structure and facilities of the hospital are related to word-of-mouth behavior. Nursing, ancillary, and administrative services are not related to word-of-mouth behavior.